Tráfico de drogas: o mercado que adota crianças e não dispensa trabalhadores : uma experiência etnográfica no município de Vitória - Possmozer, Michelli de Souza (2017)
It historically situates the marginalized contemporary child as the result of a scenario wellmarked by historical stays (NEDER, 2005) regarding the social history of childhood in Brazil. Contextualizes that the children and adolescents early attracted to provide services to the drugs trafficking in communities of Vitoria are a reflection of the capitalist system, in which the logic of homo oeconomicus (Michel Foucault) predominates. Therefore, it demystifies the legal and moralistic discourse that currently classifies the young drug dealer as the protagonist of urban violence and brings to light the neoliberal market view which moves the drugs trade in the underprivileged urban areas. In this context, it understands how the experience of children in drugs trafficking occurs, classified according to the nomenclature from the Children and Adolescents' Statute (Ecriad) with up to 12 years old. Uses the following methodological procedures, in three stages: 1) documentary research, resulting from the collection of 38 attendance logs in the Creas and Guardianship Councils, referring to children and adolescents with experience in drugs trafficking since childhood; 2) in-depth interviews with family members, institutional actors, teenagers in conflict with the law, drug dealers, ex-drug dealers and local residents; and 3) ethnography in a underprivileged community of Vitória, for a period of three months. At the end of the empirical research were established dialogues with 58 interlocutors. The results indicate that children exposed to an experience in drugs trafficking in their communities' daily routine have previously experienced a series of rights violations that contradict the Ecriad. The trafficking experience does not have the same meaning as the active involvement, because in theory the child is not recruited as a member of the trafficking activities and starts to receive a fixed amount for his work, but is called a formiguinha (a young ant), who lends favors such as buying food and items ordered by the drug dealers, in exchange for a small sum of money or snacks. The conclusions of this study point out that the formiguinhas are almost imperceptible in the drugs’ trafficking dynamics in communities, and because of that, little importance is given to them, turning the attention to teenagers, whom in general are more visible and currently constitute a larger part of the drugs trade's front line. However, while these children are living and reproducing a criminal repertory in their daily plays and spend part of their childhood lending favors to local trafficking, they are adopted by drug dealers and internalize the crime world's neoliberal logic, recognizing in the drug trafficking the promising alternative work opportunity presented to them.